Posisi komponen GPP terhadap variasi konstituen harmonik pasang surut bulan Muharram di Stasiun Sabang - Salnuddin Salnuddin; Nurhalis Wahidin; Jefry Bemba (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2018)
The movement of celestial bodies produces a variation of a gravitational gradient as a tidal generation force (GPP). Position Sabang Station, declination maximum and position lunar month of Muharram aka n generate harmonic constituent character identifier of GPP, where the water level is the sum of the amplitude of harmonic constituent that generated at a certain time.This research is to determine the variation of harmonic constituents and identify the character of harmonic constituents of GPP component position characterization in Muharram month. The results show Katrakteristik tidal movement beginning of the month of Muharram in Sabang Station occurred 1-2 hours after ijtimak.. Value riding dominant water derived from the value of Mean Sea Level ( 52%), and the dominant contribution hamonik constituents derived from component M 2 (28 - 33%). Harmonic constituents M 2 does not show the position of the moon in Muharram, while the position of the sun is reflected in the constituent phase harmonic S 2..